The Effect of Tuition Fees on University Applications: Evidence from the UK - Filipa Sá (Institute for the Study of Labor (IZA), 2014)
This article exploits variation in university tuition fees over time and across countries in the UK to examine the effect of fees on applications to higher education. It focuses on two policy changes: the removal of upfront tuition fees in Scotland in 2001 and the increase in fees in England in 2012. The findings suggest that the 2001 reform increased applications by 24.4%, while the 2012 reform reduced applications by 30.3%. The 2012 reform had a larger negative effect for applicants aged 20 and over and for courses with lower expected earnings after graduation.
Keywords: I21; J24; 330; tuition fees; university applications